Alienation and Resistance: New Possibilities for Working-Class Formation - Zamudio, Margaret (Social justice, 2004)
Part of a special issue on social justice for workers in the global economy. The processes that shape working-class formation in the U.S. service sector are investigated with an analysis of data from employers, workers, and union organizers in the hotel industry in Los Angeles, California, which is dominated by immigrant Latina/o labor. The roles that globalization, the transition from a goods-producing to a service-producing society, and the commodification of workers' identity rather than just their labor have played in creating new conditions for resistance are highlighted. It is suggested that, in an industry where race, ethnicity, and citizenship are particularly pertinent, alienation, rather than exploitation, is the better predictor of working-class resistance.